Олександр Андрійович Безбородько (1747 – 1799) - Половець, В. (Сiверянський лiтопис, 2018)
У статті подається життя та діяльність О. А. Безбородька – визначного державного діяча, дипломата, талановитого письменника і політика. Народившись у сім’ї
генерального писаря козацького війська та отримавши добру освіту в Києво-Могилянській академії, Олександр розвинув неабиякі літературні здібності, які потім стали в пригоді на державній і дипломатичній діяльності. Його феноменальна пам'ять сприяла успішному просуванню по службі. В статье освещается жизнь и деятельность А.А. Безбородька – выдающегося государственного деятеля, дипломата, талантливого писателя и политика. Родившись
в семье генерального писаря казацкого войска и получив хорошее образование в Киево-Могилянской академии, Александр развил незаурядные литературные способности,
которые потом пригодились в государственной и дипломатической деятельности.
Его феноменальная память благоприятствовала успешному продвижению по службе. O.A. Bezborodko was born on 14 March 1747 in the city of Glukhiv, Chernihiv Province
(now- Chernihiv Region) in the family of a general clerk in the Cossacks army Hetman’s
office. Besides Oleksandr, there were two more children in the family – a daughter named
Tetiana and a son named Illia. Oleksandr completed his primary education course at home
and continued his study at the Kyiv-Mohyla Academy. Upon graduation, he entered the
public service in the office of the President of Malorossiya (Little Russia) collegium of the
Governor-General of Ukraine, Count P.O. Rumiantsev. By the order of the latter, Oleksandr
was appointed commander of Malorossiskyi and Nizhynskyi, and later also Lybenskyi,
Myrhorodskyi, and Kompaniyskyi regiments in the war with Turkey (1768 – 1774). In this
military campaign, he demonstrated his bravery, intellect, and fairness, capability to find the
ways out of difficult situations. The quick turn in the life of O. Bezborodko happened not due to his military activity, but his public service. According to the recommendation of P.O. Rumiantsev, O. Bezborodko was
appointed secretary for special affairs and commissions of the Empress of Russia Catherine II.
In this capacity, he showed his capability to express his ideas in a refined manner, demonstrated
high style of writing and amazing wield of a pen. After the death of the Count M. Panin in
1873, O. Bezborodko became a member of the collegium of foreign affairs and counsellor on
the matters of foreign policy of the Russian Empire. He took an active part in creating the
system of armed neutrality of Russia having signed the Convention with Holland, Prussia,
Portugal, and Naples. He managed to combine his duties with other public affairs. He was the head of the
Post-office department, section of expedition of the Senate, was actually an acting Minister
of foreign affairs. In 1796, O. Bezborodko made the government to approve the decree on
restoration of administrative courts in Left-bank Ukraine, re-establishment of the Hetmans’
territory and Zaporizka Sich within new territorial boundaries. He is also known for his
achievements in culture. He wrote several works on the history of Ukraine, Moldova, and
Russian-Turkish wars. O. Bezborodko composed an exhaustive list of Hetmans, judges general,
and treasurers of Ukraine. In the letter to his father dated 1777, Oleksandr Bezborodko wrote
that he was collecting materials for the «History of Ruses». O. Bezborodko died at the age of
52 on 06 April 1799. According to his will, his rich heritage was used for charitable purposes.
With his money (220 000 rubles in gold), the Nizhyn lyceum was founded in his native region.
In 1875, it became the Institute for History and Philosophy named after O.A. Bezborodko,
and in 1920 – Pedagogical institute named after M.V. Gogol. Now, it is Nizhyn Gogol State University.